Fit Perception and Engagement: The Mediating Role of Work Meaningfulness - James, R. (Journals.sagepub.com/home/vis, 2021)
Research on engagement has gained considerable attention in recent years as it is a strong predictor of a range of positive individual and organizational outcomes. There is a question of why the level of the engagement is different from employee to employee in an organi zation, though they are provided with the same resources. This study aims to investigate the influence of fit perception on engagement and the role of the employee’s psychological condition (work meaningfulness) on this relationship. This study mainly employed a survey research strategy, and data were primarily garnered from a questionnaire. This study was conducted among 145 respondents from the public sector organizations in Sri Lanka. Partial least-square structural equation modelling was employed to analyse the generated data. In this study, the researcher has conceptualized fit perception as a higher order construct comprising Person Job fit and Person Organization fit. The study revealed that fit perception positively influences employee engagement, and this relationship is mediated by work meaningfulness. This study contributes to the literature by deepening the understanding of the fit perception and engagement relationship by introducing work meaningfulness as a mediator variable. By highlighting how engagement is influenced by fit perception and work meaningfulness, this study facilitates practitioners to build and maintain an engaged workforce. Further contributions of this study, the avenue for future research, and study limitations are presented in detail at the end of this article.
Keywords: Engagement; Fit Perception; Job Demand; Job Resource; Work Meaningfulness; Psychological Conditions